1998
DOI: 10.1046/j.1365-2893.1998.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Viral and host factors in the prediction of response to interferon‐α therapy in chronic hepatitis C after long‐term follow‐up

Abstract: Acute infection with hepatitis C virus (HCV) develops into a chronic hepatitis in about 50-70% of patients. Treatment of these patients with interferon-alpha (IFN-alpha) results in a sustained long-term response in only 15-20% but causes numerous unwanted side-effects in a higher percentage of patients. The aim of our study was to define host or viral parameters that would allow identification of responders and non-responders to IFN-alpha prior to the onset of treatment. We studied a group of 87 patients suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
1
26
1
Order By: Relevance
“…Among the host factors, cytokines, which are crucially involved in the regulation of antiviral immune responses, are likely candidates to affect the response to antiviral therapy. [19][20][21][22] For instance, the production of in- appropriate levels of tumor necrosis factor alpha and interleukin-10 have been reported to contribute to viral persistence and to affect response to treatment. [24][25][26] Here, we analyzed the effect of the IL-6 C174G polymorphism on response to HCV-specific treatment in patients with HIV coinfection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the host factors, cytokines, which are crucially involved in the regulation of antiviral immune responses, are likely candidates to affect the response to antiviral therapy. [19][20][21][22] For instance, the production of in- appropriate levels of tumor necrosis factor alpha and interleukin-10 have been reported to contribute to viral persistence and to affect response to treatment. [24][25][26] Here, we analyzed the effect of the IL-6 C174G polymorphism on response to HCV-specific treatment in patients with HIV coinfection.…”
Section: Discussionmentioning
confidence: 99%
“…18 However, the effect of the IL-6 polymorphism on response to HCV-specific treatment has not yet been addressed. Regarding the potentially pivotal role of host genetic factors for the outcome of anti-HCV treatment, [19][20][21][22] the current study was designed to analyze the effect of IL-6 genotypes on response to HCVspecific treatment in both HCV/HIV coinfected and HCV monoinfected patients.…”
Section: H Epatitis C Virus (Hcv) Is a Major Health Problem In Human mentioning
confidence: 99%
“…Previous research has shown that the HLA-I genes are in linkage disequilibrium with CHB and the polymorphisms of HLA-II alleles are associated with susceptibility to CHB (7). However, the association is racially and geographically dependent (6,(8)(9)(10).…”
Section: Hepatitis B Virus (Hbv) Infection Is a Serious Issuementioning
confidence: 99%
“…Previous research has shown that the HLA-I genes are in linkage disequilibrium with CHB and the polymorphisms of HLA-II alleles are associated with susceptibility to CHB (7). However, the association is racially and geographically dependent (6,(8)(9)(10).The prevalence of HBV infection is extremely high in China and many people with HBV infections develop CHB and some progress to the onset of cirrhosis (11). A follow-up study (1-18.4 years) revealed that 23 and 4.4% of CHB patients with hepatitis B early antigen (HBeAg)-negative serological status progress to the deve lopment of cirrhosis and HCC, respectively (12,13).…”
mentioning
confidence: 99%
“…Meanwhile, other studies found no difference in distribution of HLA alleles between responders and non responders to antiviral therapy, for instance, in German, Knolle et al (1998) have reported that, in patients suffering from chronic hepatitis C and treated with IFN-, the pretreatment viral factors, not host factors, were significantly correlated with treatment response. Romero-Gomez et al (2003) reported that in Spanish population, HLA class II showed no effect on response to interferon treatment.…”
Section: ) -------------------------------------------------------mentioning
confidence: 92%